STUDENTS’ PERCEPTIONS ON EDUCATORS’ DIGITAL LITERACY IN TEACHING - Nainggolan, Inka Enrika Sintikhe; Rini, Sri Endah Setia (Conscientia - Journal on Language, Literature, and Culture, 2025)
The COVID-19 pandemic significantly transformed the educational landscape, compelling educators to adopt various digital tools to ensure the continuity of learning. Although face-to-face learning has resumed, the integration of technology in education remains relevant and essential. This study investigates students' perceptions of lecturers' digital literacy in the context of online learning during and after the pandemic. The research involved 30 respondents through questionnaires and 7 participants in forum group discussions (FGDs) from two higher education institutions with language departments: STBA LIA Yogyakarta and Universitas Negeri Yogyakarta. The study aimed to assess lecturers' competencies in using digital tools for teaching and the extent to which these tools are considered necessary from the students’ perspective. The findings indicate that while lecturers demonstrate sufficient to proficient skills in utilizing Learning Management Systems (LMS), video conferencing platforms, and basic hardware tools such as laptops and smartphones, they often struggle with more advanced competencies, including video and audio editing, gamification, and managing digital learning platforms. Students emphasized the importance of engaging teaching materials, particularly video-based content with high resolution and clear audio, to support better understanding in online settings. Furthermore, students highlighted the necessity for lecturers to master not only the delivery of content but also the management of digital classroom tools, including online attendance, evaluation, and communication through messenger platforms. The study concludes that digital literacy among lecturers must continue to be developed even after the pandemic, as online and blended learning remain integral to modern education. Mastery of digital tools—ranging from authoring and testing tools to communication and presentation platforms—is crucial in enhancing the quality and accessibility of education. Ongoing training and professional development in educational technology are recommended to ensure that lecturers can meet the evolving needs of their students in a digital learning environment.